Effect of Non-Pharmacological Pain Management Methods on Reduction the Duration of Labor Stages in Primigravida Women at AL-Elwyia Maternity Teaching Hospital - Fadhil, Sarab; ali, rabea (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: To evaluate the effect of non-pharmacological pain relief methods on duration of labor stage. Methodology: A quasi-experimental study design was conducted during the period of (4th July 2018 through 24th October 2018) on non-probability of (60) women (30) of them were a control group and (30) were the study group whom admitted to Al-Elwyia Maternity Teaching Hospital suffering from labor pain. A questionnaire was used as a tool of data collection Descriptive& Inferential statistical analyses were used to analyze the data. Result: The highest percentages of study and control groups were in age group (< 20) years old, primary schools graduates, housewife, from "urban area", within low category of socioeconomic scale, at gestational age between (39 weeks – 40 weeks +6day), and have intact membrane status .Also there are highly significant differences concerning durations of the (1st, 2nd, and 3rd) stages of labor among study and controlled groups at (P=0.001),(P=0.002),&( at (P=0.000) respectively. Recommendation: The study recommended to conduct structured training programmed for all midwives in maternity hospitals and primary health care centers to enable them to implement the non-pharmacological pain relief methods, in addition a simplified guideline for midwife should be disrupted and contains information about the proper use of non-pharmacological pain management methods and its advantages